2017
DOI: 10.4291/wjgp.v8.i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease: Diagnostic biomarkers

Abstract: Nonalcoholic fatty liver disease is a common medical condition worldwide and its prevalence has increased notably in the past few years due to the increases in prevalence of obesity and metabolic syndrome. However, diagnosis of this disease is still a matter of debate because of disease variations and pathophysiologic alterations. Specific single markers have gained considerable attention recently, among them markers related to hepatic pathophysiology, inflammation, adipocytokines and so forth. But, it seems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 147 publications
(281 reference statements)
7
89
0
9
Order By: Relevance
“…However, this observation is not mandatory (16). The diagnostic value of ALT for NASH is still controversial and is based on unclear study results (17). In our study, the activity of ALT in rats in the HFD group is increased compared to rats in the NFD group.…”
Section: Discussionmentioning
confidence: 53%
“…However, this observation is not mandatory (16). The diagnostic value of ALT for NASH is still controversial and is based on unclear study results (17). In our study, the activity of ALT in rats in the HFD group is increased compared to rats in the NFD group.…”
Section: Discussionmentioning
confidence: 53%
“…"a" versus Control rats (Group I) and "d" versus NASH (Group VII) rats. The symbol "&, @, *" represent the statistical significance levels at p < .001, p < .01, and p < .05 accordingly hepatocyte injury releases such markers into the bloodstream and indicates the abnormality of the liver and is noticed to be elevated in rats fed with the MCD diet (Hadizadeh et al, 2017). The co-and pre-administration of the nutrient mixture to steatosis rats resulted in the decrease of all of these markers, indicating the role of the nutrient mixture as a hepatoprotective agent by reducing the damage done to the hepatocytes by other metabolic factors (Cunningham et al, 2018;Kargulewicz et al, 2014).…”
Section: F I G U R E 8 (A)mentioning
confidence: 99%
“…Several reports have demonstrated that liver steatosis is associated with the elevation of certain clinical and biochemical markers with low predictive potential. Indeed, transaminases and specifically alanine aminotransferase (ALT) commonly used as liver damage markers are not 100% reliable because some patients suffering from NAFLD do not present high levels of ALT . Recent studies evaluating other biomarkers including circulating microRNA reported promising results, although larger studies are still necessary to validate them in the future.…”
Section: Nafld a Common Disease Affecting The Use Of Steatotic Graftmentioning
confidence: 99%